Reading Anxiety, Reading Self-Efficacy And Vocabulary As Predictors Of Students’ Reading Comprehension - Hasriati, Hasriati; Sidu Marafat, La Ode; Lio, Asrun (Halu Oleo University, 2017)
Many students assumed reading is not difficult process. In fact, reading process is not merely their understanding of each word and the surface structure denoted in a text, but it also includes the process of comprehension. Unfortunately, they also do not realize that during this process, reading anxiety, reading self-efficacy and vocabulary have been stated as some contributing factors. Thus, the current study examined whether reading anxiety, reading self-efficacy and vocabulary contribute towards students’ reading comprehension and which one of these factors that serves as the better predictor of students’ reading comprehension among 82 students of second semester of English department of Halu Oleo University. Questionnaires are employed for measuring students’ reading anxiety and reading self-efficacy, vocabulary test for measuring students’ vocabulary. Whereas, reading comprehension test for measuring students’ reading comprehension. The result revealed reading anxiety contributes towards students’ reading comprehension, reading self-efficacy contributes towards students’ reading comprehension and vocabulary contributes towards students’ reading comprehension. Vocabulary is higher than reading anxiety and reading self-efficacy in predicting students’ reading comprehension when these factors are examined simultaneously. Importantly, this study leads to the conclusion that vocabulary is better and stronger predictor of students’ reading comprehension than students’ reading anxiety and students’ reading self-efficacy. Taking importance of vocabulary into consideration, therefore language teachers should put more emphasize on students’ vocabulary, particularly endeavor to make their vocabulary knowledge wider and deeper.